2014
DOI: 10.2147/ijn.s54171
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in relation to peptide and protein aggregation

Abstract: Over the past two decades, there has been considerable research interest in the use of nanoparticles in the study of protein and peptide aggregation, and of amyloid-related diseases. The influence of nanoparticles on amyloid formation yields great interest due to its small size and high surface area-to-volume ratio. Targeting nucleation kinetics by nanoparticles is one of the most searched for ways to control or induce this phenomenon. The observed effect of nanoparticles on the nucleation phase is determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 112 publications
0
26
0
Order By: Relevance
“…The effects of nanoparticles on protein aggregation may vary, depending on the physicochemical nature of the nanoparticles and the protein in question 18,19 . Past studies showed that GO nanosheets exerted an inhibitory effect on the aggregation of amyloid-β 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The effects of nanoparticles on protein aggregation may vary, depending on the physicochemical nature of the nanoparticles and the protein in question 18,19 . Past studies showed that GO nanosheets exerted an inhibitory effect on the aggregation of amyloid-β 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Fig 8A and 8B represents the far-UV CD spectra of HSA and BSA at 1:0, 1:5 and 1:10 protein to NDGA molar ratio. In the absence of NDGA, HSA and BSA exhibits two characteristic peak which are around at 222 nm (n→pi* transition) and 208 nm (pi→pi* transition), a characteristic of α-helix [ 52 , 53 ]. The spectra in the Fig 8A and 8B depicts that NDGA interaction with HSA (& BSA) led to a change in secondary structure of albumin resulting into the increment in helical content of protein.…”
Section: Resultsmentioning
confidence: 99%
“…These applications encompass them to be used in electronic, drug delivery, optical, mechanics, catalysis, bio-encapsulation and wastewater treatment especially adsorption [4][5][6][7][8][9][10][11][12][13][14][15]. Besides all these properties, nano-particles have some toxic effects for aquatic and human health.…”
Section: Classification Of Nano-materialsmentioning
confidence: 99%